Ameliorative effect of Ruzu herbal bitters on high-fat diet induced non-alcoholic fatty liver disease in Wistar rats - Olubanke O. Ogunlana; Babatunde O. Adetuyi; Tobi S. Adekunbi; Bose E. Adegboye; Franklyn N. Iheagwam; Oluseyi E. Ogunlana (GarVal Editorial Ltda., 2021)
Context: One of the world's most widespread and frequent liver diseases is the non-alcoholic fatty liver disease (NAFLD). Aims: To evaluate the preventives activities of Ruzu herbal bitters (RHB), which is an anti-obesity therapeutic concoction used widely in Nigeria on high-fat diet (HFD) induced NAFLD in albino Wistar rats. Methods: A total number of twenty-five rats were isolated and divided equally into five groups. Group 1, the normal control group was placed on normal rat diet and normal saline (1 mL/kg body weight daily) for twelve weeks. The remaining four groups 2-5 were placed on HFD for twelve weeks; adding to the following treatment schedules by oral gavage: group 2 received pioglitazone 4 mg/kg daily, group 3 received RHB 0.6 mL/kg daily, group 4 received normal saline 1 mL/kg daily and group 5 received fenofibrate 10 mg/kg daily (s.c). The animals were sacrificed and biochemical markers of liver function, lipid profile, glycemic index, and histopathological assessment of the liver of the rats were determined. Results: Rat treated with RHB and other treated groups significantly (p<0.05) reduced the liver index, fasting blood glucose, and activities and concentrations of liver function enzymes and molecules when compared to untreated NAFLD group. Scoring of hepatic steatosis also showed the ameliorative role of the treatment on NAFLD. Conclusions: This study reveals that RHB and other treatment options assessed could prevent HFD-induced NAFLD and could be explored as another therapeutic approach to fenofibrate and pioglitazone in NAFLD management.